2007
DOI: 10.1074/jbc.m701078200
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Amyloid-β Fibrillization Reduces Oligomer Levels and Functional Deficits in Alzheimer Disease Mouse Models

Abstract: Many proteins suspected of causing neurodegenerative diseases exist in diverse assembly states. For most, it is unclear whether shifts from one state to another would be helpful or harmful. We used mutagenesis to change the assembly state of Alzheimer disease (AD)-associated amyloid-␤ (A␤) peptides. In vitro, the "Arctic" mutation (A␤E22G) accelerated A␤ fibrillization but decreased the abundance of nonfibrillar A␤ assemblies, compared with wild-type A␤. In human amyloid precursor protein (hAPP) transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
364
3
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 392 publications
(416 citation statements)
references
References 70 publications
40
364
3
6
Order By: Relevance
“…Moreover, it needs to be seen whether compound-induced accelerated deposition of A42 aggregates has beneficial effects on disease pathogenesis in AD models. Experimental evidence supporting such a view has been presented previously, indicating that accelerated A fibrillization reduces oligomer levels and functional deficits in AD mouse models 49 . We suggest that compounds like O4, which bind to -sheet-rich amyloid structures might reduce their toxicity by preventing the abnormal interactions of small aggregate species with cellular proteins.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, it needs to be seen whether compound-induced accelerated deposition of A42 aggregates has beneficial effects on disease pathogenesis in AD models. Experimental evidence supporting such a view has been presented previously, indicating that accelerated A fibrillization reduces oligomer levels and functional deficits in AD mouse models 49 . We suggest that compounds like O4, which bind to -sheet-rich amyloid structures might reduce their toxicity by preventing the abnormal interactions of small aggregate species with cellular proteins.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, it also remains unclear whether h-αSyn WT can alter Aβ-induced phenotypes, considering the distinct properties of αSyn A30P (54). Second, despite previous evidence reporting the association of Aβ oligomers and cognitive deficits in J20 mice before plaque formation (55), the in vivo results presented here cannot rule out the possibility that the potentiation of the memory impairments seen in J20×TgI2.2 bigenic mice is a result of the overexpression of APP in these mice (i.e., ∼threefold over endogenous APP). However, recent analyses using single-cell qPCR revealed that individual neurons in sporadic AD can harbor an averaged copy number for APP of 3.8-4 (up to 12 copies) over control samples (56), suggesting that the threefold elevation of APP seen in J20 mice might actually be relevant to AD.…”
Section: Synapsin-i/ii Lowering and Cognitive Deficits In Ad And Animalmentioning
confidence: 89%
“…2). To identify A␤-42 changes in Tg2576 mice, we used four different antibodies: (1) A␤-42 antibody 6E10, which recognizes all forms (monomers, oligomers, and fibrils) of A␤-42 and a great variety of APP metabolites (Cheng et al, 2007); (2) A␤-42 antibody A11, which recognizes A␤-42 oligomers and other oligomers, such as ␣-synuclein (Kayed et al, 2003); (3) APP antibody (ab15272, Abcam), which recognizes the N-terminal portion of the APP (this antibody does not recognize A␤-42); and (4) ␣-synuclein antibody (Santa Cruz Biotechnology), which recognizes ␣-synuclein.…”
Section: Resultsmentioning
confidence: 99%